KEMAMPUAN MEMBACA SISWA SMP YANG BERMUKIM DI SEKITAR SUNGAI DI KOTA BANJARMASIN - Jumadi Jumadi (Universitas Lambung Mangkurat, 2018)
AbstractJunior High School students’ reading skills based around the River in the city of Banjarmasin.Advances in information technology make the world seem so narrow. Through print and electronicmedia, the information comes from an area quickly spread and can be accessed by residents in otherareas. These symptoms necessarily has to be anticipated with completion of reading skills, especiallysince they were sitting on the bench of the school. This research describes: (a) the level of Junior HighSchool students ‘ reading skills who settled in the area of the environment of the River in the city ofBanjarmasin; and the image of interest, read the implementation of learning to read, and the availabilityof means of learning to read in Junior High School who were around the area of the River in the city ofBanjarmasin. This research includes research of fusion (blanded), between quantitative and qualitativeresearch. Data source this study are students and teachers from five schools, i.e. SMPN 2 Banjarmasin,SMPN 4 Banjarmasin, SMPN 26 Banjarmasin,, Kanaan Christian Junior High School, SMP KartikaV-3 Banjarmasin. Engineering data collection carried through tests and nontes. Qualitative data wereanalyzed using the program EXCEL and qualitative data were analyzed based on the analysis of the text.The results showed: (1) literary reading skills of students score of 69% (classified as being); interpretivereading ability score of 43% (belongs to very low); and score reading skills comprehensively of 58%(classified low); (2) the interest of Junior High School students read the classified medium; the timeportion is considered quite memabaca; most of the teachers do not give special reading exercises forstudents; most teachers never hold/includes students in the race to read; availability of books in-schoolpackage is considered already sufficient; dictionaries available to support the implementation of learningto read in school is still lacking; and the availability of newspapers and magazines in school are also stilllacking.Key words: ability, reading, literary, interpretive, river environmentAbstrakKemampuan Membaca Siswa SMP yang Bermukim di Sekitar Sungai di Kota Banjarmasin.Kemajuan teknologi informasi membuat dunia seolah begitu sempit. Melalui media cetak danelektronik, informasi yang berasal dari suatu wilayah secara cepat menyebar dan dapat diakses olehpenduduk di wilayah lain. Gejala tersebut tentu harus diantisipasi dengan penyiapan kemampuanmembaca, terutama sejak mereka duduk di bangku sekolah. Penelitian ini mendeskripsikan tentang:235(a) tingkat kemampuan membaca siswa SMP yang bermukim di daerah lingkungan sungai di KotaBanjarmasin; dan gambaran minat baca, pelaksanaan pembelajaran membaca, dan ketersediaan saranapembelajaran membaca di SMP yang berada di sekitar daerah sungai di Kota Banjarmasin. Penelitianini termasuk penelitian perpaduan (blanded), antara penelitian kuantitatif dan kualitatif. Sumber datapenelitian ini adalah para siswa dan guru dari lima sekolah, yakni SMPN 2 Banjarmasin, SMPN 4Banjarmasin, SMP 26 Banjarmasin, SMP Kristen Kanaan, dan SMP Kartika V-3 Banjarmasin. TeknikPengumpulan data dilakukan melalui tes dan nontes. Data kualitatif dianalisis dengan menggunakanprogram EXCEL dan data kualitatif dianalisis berdasarkan analisis teks. Hasil penelitian menunjukkan:(1) skor kemampuan membaca literer siswa sebesar 69% (tergolong sedang); skor kemampuan membacainterpretif sebesar 43% (tergolong sangat rendah); dan skor kemampuan membaca secara komprehensifsebesar 58% (tergolong rendah); (2) minat membaca para siswa SMP tergolong sedang; porsi waktumemabaca dianggap cukup; sebagian besar guru tidak memberi latihan khusus membaca bagi parasiswa; sebagaian besar guru tidak pernah mengadakan/mengikutsertakan siswa dalam lomba membaca;ketersediaan buku paket di sekolah dianggap sudah cukup; ketersediaan kamus untuk menunjangpelaksanaan pembelajaran membaca di sekolah masih kurang; dan ketersediaan koran dan majalah disekolah juga masih kurang.Kata-kata kunci: kemampuan, membaca, literer, interpretif, lingkungan sungai